Carbide transition layer-diamond layer composite layer structure and preparation method thereof
By depositing a carbide gradient layer and diamond layer on the surface of tantalum and its alloys, and etching the micro-nano structure using femtosecond laser technology, the problem of rapid material failure in tantalum and its alloys in high temperature environments is solved, and a composite layer structure with high hardness, wear resistance and thermal shock resistance is achieved.
Patent Information
- Application Number
- CN202411750285.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Tantalum and its alloys are prone to rapid failure of the material surface under high temperature or rapid heating environments, resulting in a shortening of the service life of the components, and it is difficult for the prior art to achieve long-term stable use in extremely complex environments.
The composite layer structure of the carbide transition layer-diamond layer is adopted, and the carbide gradient layer is deposited by microwave plasma chemical vapor deposition method, and the micro-nano structure is etched using femtosecond laser technology on its surface to improve the adhesion of the diamond layer and the overall thermal shock resistance.
The high hardness, high wear resistance and excellent overall thermal shock resistance of the surface of tantalum and its alloys are achieved, which significantly improves the service life of the material and the stability in extreme environments.
Smart Images

Figure CN119753643A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of diamond coatings, and in particular to a composite layer structure of a carbide transition layer-diamond layer and a preparation method thereof. Background Art
[0002] In the aerospace and defense military industries, many key components need to be used in extremely complex environments with the interaction of multiple processes such as heat, mechanics and chemistry, which puts more stringent requirements on the comprehensive performance of key parts or component materials. With the development of new generation fighters and aerospace engines and other technical fields, it is an urgent need for materials to have high wear resistance, abrasion resistance and thermal shock resistance in high temperature or rapidly heated environments.
[0003] Tantalum and its alloys are known as strategic materials with high heat resistance and strength. Currently, they are widely used in rocket engines, turbine blades, turbine disks and other components, and have great application and development prospects. However, due to the low hardness of tantalum and its alloys, when subjected to severe friction and wear conditions, the surface of the material will fail quickly, the protection of the components will be lost, the service life of key components will be sharply shortened, and the application of tantalum and its alloys in aerospace and military is restricted.
[0004] In the prior art, surface strengthening of tantalum and its alloys can improve their wear resistance. For example, surface heat treatments such as carburizing and nitriding are performed on the surface of tantalum and its alloys to improve their surface hardness and wear resistance. However, the performance improvement achieved by this process technology is single and cannot meet the needs of long-term stable use in extremely complex environments. Diamond film has extremely high hardness, excellent tribological properties and high thermal conductivity. Introducing it into the surface protection of tantalum and its alloys can comprehensively improve the service performance under high temperature or rapid temperature rise. However, due to the inherent physical and chemical property differences between tantalum and its alloys and diamond, this will reduce the bonding strength of the film-substrate, the quality of diamond growth, the overall thermal shock resistance and reliability. At the same time, the current research often uses physical and chemical methods to pre-treat the substrate, using mechanical grinding and acid-base corrosion to form scratches and pits on the substrate surface to improve the adhesion of the diamond film during deposition. However, there are problems of unevenness and contamination of the prepared diamond film, and there is an urgent need for improvement in the prior art process. Summary of the invention
[0005] In view of this, the present invention proposes a composite layer structure of a carbide transition layer-diamond layer and a preparation method thereof, and utilizes the film-substrate transition layer structure to reduce the physicochemical difference between the metal matrix and the diamond, alleviate material stress, and achieve a smooth gradual change in properties and performance; at the same time, the film-substrate transition layer is pre-treated by precision machining technology femtosecond laser to construct a highly ordered micro-nano structure, which can effectively solve the defects of the film-substrate micro-layered structure, overcome the problem of low diamond nucleation growth at the deposition interface, alleviate film-substrate thermal shock, and achieve high surface hardness, high wear resistance and excellent overall thermal shock resistance of tantalum and its alloys.
[0006] The technical solution of the present invention is implemented as follows: On the one hand, the present invention provides a composite layer structure of a carbide transition layer-diamond layer, comprising: a tantalum substrate; a carbide gradient layer deposited on the surface of the tantalum substrate, wherein the C atom content in the carbide gradient layer gradually decreases toward the tantalum substrate; and a diamond layer deposited on the surface of the carbide gradient layer.
[0007] In order to further improve the film-base bonding strength, the existing process methods are to use physical and chemical methods. The physical method mostly uses mechanical grinding to produce a large number of irregular scratches on the substrate surface to increase the adhesion of diamond during the deposition process. However, the surface roughness of the diamond film deposited in this way is relatively large. The chemical method uses an acid-base two-step method to corrode the substrate surface, thereby increasing the adhesion of diamond. However, the residual chemical agents will contaminate the deposited diamond film, resulting in an impure film problem.
[0008] Specifically, the present invention uses a pre-process to carburize the tantalum substrate before depositing the diamond film, and tantalum carbide is generated on the surface of the tantalum substrate as a transition layer, forming a smooth transition layer in structure and composition, thereby solving the defect of a large difference in physical and chemical properties between tantalum and diamond. The transition layer presents a gradient change in composition, which can reduce the stress between the film and the substrate.
[0009] At the same time, based on the above technical solution, preferably, the components of the carbide gradient layer are TaC and Ta 2 C.
[0010] On the basis of the above technical solution, preferably, a plurality of grooves are etched on the surface of the carbide gradient layer.
[0011] Specifically, after the carburizing process and before depositing the diamond film, the present invention uses a precise surface processing technology, femtosecond laser, to process the surface of the carburized sample, and efficiently prepares grooves of micro-nano structures on the surface. These structures have been proven to significantly enhance the bonding ability, erosion resistance and thermal shock resistance of the tantalum base and diamond.
[0012] On the basis of the above technical solution, preferably, the tantalum substrate is a pure tantalum sheet or a tantalum alloy.
[0013] On the other hand, the present invention also provides a method for preparing a composite layer structure of a carbide transition layer-diamond layer, comprising the following steps:
[0014] S1, tantalum substrate surface polishing;
[0015] S2, carbonization treatment of tantalum substrate: placing the tantalum substrate in a reaction chamber of a microwave plasma chemical vapor deposition device, bombarding the substrate with hydrogen plasma, etching and removing surface impurities, and then introducing carbon source gas to deposit a carbide gradient layer;
[0016] S3, placing the carburized tantalum substrate in a femtosecond laser device, and etching a plurality of transverse and longitudinal intersecting grooves on the surface of the carbide gradient layer;
[0017] S4, placing the tantalum substrate after etching in step S3 in a reaction chamber of a microwave plasma chemical vapor deposition device, introducing a carbon source gas to deposit a diamond layer, and obtaining a composite layer of a carbide transition layer-diamond layer on the tantalum substrate.
[0018] On the basis of the above technical scheme, preferably, in step S2, the reaction chamber is evacuated to below 1 Pa, 300 sccm of hydrogen is introduced, the microwave power is adjusted to 4250-5000 W, the cavity pressure is 18-22 KPa, the temperature is 600-750°C, and the substrate is bombarded by hydrogen plasma for 15-25 minutes to etch and remove impurities.
[0019] On the basis of the above technical scheme, preferably, during the carbonization treatment in step S2, the microwave power is 4250-5000W, the deposition time is 3-6h, the carbonization deposition temperature is 850-1050°C, and the atomic percentage of carbon atoms in the reaction chamber is 0.5%-2%.
[0020] On the basis of the above technical solution, preferably, in step S3, the laser power is 10-15 W, the scanning period is 20-30 μm, the scanning speed is 5-8 mm / s, and the number of scans is 4-6 times.
[0021] Based on the above technical solution, preferably, in step S3, the groove depth is 4-6 μm.
[0022] On the basis of the above technical scheme, preferably, in step S4, when the diamond layer is deposited, the atomic percentage of carbon atoms in the reaction chamber is 2.5%-5%, the cavity pressure is 8-10KPa, the microwave power is 4250-5000W, the deposition time is 4-8h, and the deposition temperature is 750-850℃.
[0023] The composite layer structure of a carbide transition layer-diamond layer and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:
[0024] (1) First, the present invention utilizes the activation effect, diffusion effect and sputtering effect of microwave plasma to perform efficient plasma carbonization treatment on the substrate, and prepares a carbide layer with a gradient distribution of components and a smooth structural transition on the surface of the substrate. The surface layer of the carbide layer provides a CC bond that can be tightly bonded to the diamond layer at the atomic level, thereby achieving a high bonding strength between the substrate material and the diamond layer. At the same time, since the thermal expansion coefficient of the carbide layer is between the thermal expansion coefficient of the film base, it shows a gradient change, which can play a role in reducing the internal stress of the film base.
[0025] (2) Secondly, the present invention uses femtosecond laser technology to form a highly ordered micro-nano structure in the carburized transition layer. On the one hand, the deposition and adhesion of carbon atoms is improved, avoiding the density difference and pollution problems caused by the traditional physical and chemical methods of increasing the deposition and adhesion of diamonds, and greatly improving the nucleation density of the diamond film and the film-base bonding force. On the other hand, the microscopic interlocking of the carbide layer and the diamond is achieved, and the carbide and diamond at the interface are staggered and the dislocation increases, thereby achieving interface strengthening, which can effectively buffer the long-term severe friction and impact experienced by the surface during the use of the force effect, and prevent the cracks from extending to the matrix; in the thermal effect environment, the temperature of the component will rise sharply, of which about one-fifth of the heat is absorbed by the workpiece material, and the thermal action time is 10 microseconds. The heat on the workpiece surface has no time to transfer outward. Due to the large difference in thermal expansion coefficients between the film and the substrate, there is a large temperature gradient, and the resulting thermal stress will cause the diamond film to fall off. The micro-nano structure of the carburized transition layer prepared by the present invention can increase the heat transfer area between the film and the substrate, improve the heat dissipation efficiency, alleviate the thermal conductivity difference between metal and diamond, reduce the thermal stress caused, and thus improve the overall thermal shock resistance.
[0026] (3) Finally, the present invention utilizes microwave plasma chemical vapor deposition, which uses waveguides to transmit plasma generated by microwave excitation, and there is no impurity source in the synthesis process. By adjusting the process parameters for depositing diamond thin films, the diamond film efficiently prepared has the advantages of high quality purity and no pollution. At the same time, the microwave deposition temperature is relatively low, so the thermal mismatch between the epitaxial layer and the substrate and the stress generated are small. Combined with the multilayer structure of nano-scale grains prepared by the present invention, it is beneficial to reduce the internal stress of the film layer and improve the hardness of the film layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 The present invention is a schematic diagram of the preparation process of the composite layer of carbide transition layer-diamond layer, wherein (a) is a tantalum substrate, (b) is a carburizing treatment, (c) is a femtosecond laser etching, and (d) is a deposited diamond layer. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The composite layer structure of the carbide transition layer / diamond layer of the present invention comprises a tantalum substrate, a carbide gradient layer is deposited on the surface of the tantalum substrate by a microwave plasma chemical deposition method, a groove is subsequently etched on the surface of the deposited carbide gradient layer by a femtosecond laser device, and then a diamond layer is deposited on the surface of the carbide gradient layer by a microwave plasma chemical deposition method to obtain a composite layer of the carbide transition layer-diamond layer. The specific preparation method is described in detail by the following examples.
[0031] Example 1
[0032] The composite layer structure of the carbide transition layer / diamond layer and the preparation method thereof of this embodiment include the following steps:
[0033] S1, grinding and polishing of tantalum substrate and its surface. The size of the tantalum substrate used in the present invention is 13.5mm×13.5mm×2.7mm (length, width and thickness), but is not limited to tantalum substrates of other specific sizes. The purity level of the tantalum substrate is 3N5 and above, the purity is above 99.95%, and the total content of metal impurities does not exceed 500ppm. The material of the tantalum substrate is not limited to pure tantalum, including a series of tantalum alloys, such as Ta-2.5W, Ta-10W, Ta-40Nb, etc. This embodiment is a pure tantalum sheet. The surface of the sample is polished with 240, 400, 800, 1000, 1500, 2000, 3000, 5000, and 7000 mesh sandpaper in turn, and then the surface of the sample is polished with 9, 3, 1, and 0.05μm polishing cloth in turn to obtain a tantalum substrate with a mirror surface. For the grinding and polishing standards of the sample, refer to GB / T 13298-2015.
[0034] S2, the tantalum substrate is carbonized: the tantalum substrate treated in step S1 is placed in the reaction chamber of the microwave plasma chemical vapor deposition equipment. Prior to this, the reaction chamber needs to be wiped with anhydrous ethanol and blown dry with helium. Then, the reaction chamber is evacuated to below 1Pa, 300sccm of hydrogen is introduced, the microwave power is adjusted to 5000W, the cavity pressure is maintained at 22KPa, the temperature is controlled at 750°C, the substrate is bombarded with hydrogen plasma for 20min, and the impurities on the surface are etched and further removed; then, a carbon source gas is introduced and the gas flow rate is adjusted to deposit a carbide gradient layer, the microwave power is 5000W, the deposition time is 6h, the carbonization deposition temperature is 1050°C, and the atomic percentage of carbon atoms in the mixed gas in the reaction chamber is 2%; a carbide gradient layer on the tantalum surface is obtained, and the C atom content of the carbide layer gradually decreases as it approaches the tantalum surface, and the carbide gradient layer is TaC and Ta 2 C.
[0035] S3, femtosecond laser surface pretreatment of the carburized sample: the carburized sample treated in step S2 is placed in a femtosecond laser device, and a well-shaped papillary periodic micro-nanostructure array with a depth of 6 μm and an aspect ratio of 2-2.5 is prepared with laser parameters of 15 W laser power, 30 μm scanning period, 8 mm / s scanning speed, and 6 scanning times.
[0036] S4, deposition of a diamond layer on the carbide layer of tantalum: the tantalum substrate sample with a carbide layer generated on the surface after the treatment in step S2 does not need to be taken out, and the flow rate of the carbon source gas is adjusted so that the atomic percentage of carbon atoms in the mixed gas in the reaction chamber is 5%, and the diamond layer is deposited. The cavity pressure is maintained at 10KPa, the microwave power is 5000W, the deposition time is 8h, and the carbide deposition temperature is 850°C. A composite layer of a carbide transition layer / diamond layer is obtained on the tantalum substrate. The carbon source gas and microwave power are turned off, and hydrogen is continued to be introduced to cool the reaction system to room temperature at a rate of 15°C / min. Finally, the hydrogen is turned off, the air pressure in the reaction chamber is adjusted to atmospheric pressure, and the sample is taken out.
[0037] Example 2
[0038] The composite layer structure of the carbide transition layer / diamond layer and the preparation method thereof of this embodiment include the following steps:
[0039] S1, the tantalum substrate and its surface grinding and polishing treatment are the same as in the embodiment.
[0040] S2, the tantalum substrate is carbonized: the tantalum substrate treated in step S1 is placed in the reaction chamber of the microwave plasma chemical vapor deposition equipment. Prior to this, the reaction chamber needs to be wiped with anhydrous ethanol and blown dry with helium. Then, the reaction chamber is evacuated to below 1Pa, 300sccm of hydrogen is introduced, the microwave power is adjusted to 4500W, the cavity pressure is maintained at 20KPa, the temperature is controlled at 700℃, and the substrate is bombarded with hydrogen plasma for 20min to etch and further remove impurities on the surface; then, a carbon source gas is introduced and the gas flow rate is adjusted to deposit a carbide gradient layer, the microwave power is 4500W, the deposition time is 4h, the carbonization deposition temperature is 950℃, and the atomic percentage of carbon atoms in the mixed gas in the reaction chamber is 1%; a carbide gradient layer on the tantalum surface is obtained, and the C atom content of the carbide layer gradually decreases as it approaches the tantalum surface. The carbide gradient layer is TaC and Ta 2 C.
[0041] S3, femtosecond laser surface pretreatment of the carburized sample: the carburized sample treated in step S2 is placed in a femtosecond laser device, and a papillary periodic micro-nanostructure array with a depth of 5 μm and an aspect ratio of 2.25 is prepared with laser parameters of 12 W laser power, 25 μm scanning period, 6 mm / s scanning speed, and 5 scanning times.
[0042] S4, deposition of a diamond layer on the carbide layer of tantalum: the tantalum substrate sample with a carbide layer generated on the surface after the treatment in step S2 does not need to be taken out, and the flow rate of the carbon source gas is adjusted so that the atomic percentage of carbon atoms in the mixed gas in the reaction chamber is 3%, and the diamond layer is deposited. The cavity pressure is maintained at 9KPa, the microwave power is 4500W, the deposition time is 6h, and the carbide deposition temperature is 800°C. A composite layer of a carbide transition layer / diamond layer is obtained on the tantalum substrate. The carbon source gas and microwave power are turned off, and hydrogen is continued to be introduced to cool the reaction system to room temperature at a rate of 15°C / min. Finally, the hydrogen is turned off, the air pressure in the reaction chamber is adjusted to atmospheric pressure, and the sample is taken out.
[0043] Example 3
[0044] The composite layer structure of the carbide transition layer / diamond layer and the preparation method thereof of this embodiment include the following steps:
[0045] S1, the tantalum substrate and its surface grinding and polishing treatment are the same as in the embodiment.
[0046] S2, the tantalum substrate is carbonized: the tantalum substrate treated in step S1 is placed in the reaction chamber of the microwave plasma chemical vapor deposition equipment. Prior to this, the reaction chamber needs to be wiped with anhydrous ethanol and blown dry with helium. Then, the reaction chamber is evacuated to below 1Pa, 300sccm of hydrogen is introduced, the microwave power is adjusted to 4250W, the cavity pressure is maintained at 18KPa, the temperature is controlled at 600℃, the substrate is bombarded with hydrogen plasma for 20min, and the impurities on the surface are etched and further removed; then, a carbon source gas is introduced and the gas flow rate is adjusted to deposit a carbide gradient layer, the microwave power is 425W, the deposition time is 3h, the carbonization deposition temperature is 850℃, and the atomic percentage of carbon atoms in the mixed gas in the reaction chamber is 0.5%; a carbide gradient layer on the tantalum surface is obtained, and the C atom content of the carbide layer gradually decreases as it approaches the tantalum surface, and the carbide gradient layer is TaC and Ta 2 C.
[0047] S3, femtosecond laser surface pretreatment of the carburized sample: the carburized sample treated in step S2 is placed in a femtosecond laser device, and a papillary periodic micro-nanostructure array with a depth of 4 μm and an aspect ratio of 2 is prepared with laser parameters of 10 W laser power, 20 μm scanning period, 5 mm / s scanning speed, and 4 scanning times.
[0048] S4, deposition of a diamond layer on the carbide layer of tantalum: the tantalum substrate sample with a carbide layer generated on the surface after the treatment in step S2 does not need to be taken out, and the flow rate of the carbon source gas is adjusted so that the atomic percentage of carbon atoms in the mixed gas in the reaction chamber is 2.5%, and the diamond layer is deposited. The cavity pressure is maintained at 8KPa, the microwave power is 4250W, the deposition time is 4h, and the carbide deposition temperature is 750°C. A composite layer of a carbide transition layer / diamond layer is obtained on the tantalum substrate. The carbon source gas and microwave power are turned off, and hydrogen is continued to be introduced to cool the reaction system to room temperature at a rate of 15°C / min. Finally, the hydrogen is turned off, the air pressure in the reaction chamber is adjusted to atmospheric pressure, and the sample is taken out.
[0049] Example 4
[0050] The difference between Example 4 and Example 1 is that the tantalum substrate is made of Ta-2.5W tantalum alloy.
[0051] Example 5
[0052] The difference between Example 5 and Example 2 is that the tantalum substrate is made of Ta-2.5W tantalum alloy.
[0053] Example 6
[0054] The difference between Example 6 and Example 3 is that the tantalum substrate is made of Ta-2.5W tantalum alloy.
[0055] Comparative Example 1
[0056] The difference between Comparative Example 1 and Example 1 is that steps S2 and S3 are omitted, and a diamond layer is directly deposited on the surface of the pure tantalum sheet.
[0057] Comparative Example 2
[0058] The difference between Comparative Example 2 and Example 1 is that the S3 step is missing, and the diamond layer is deposited directly on the carbide gradient layer.
[0059] Comparative Example 3
[0060] The difference between Comparative Example 3 and Example 1 is that steps S3 and S4 are missing, and only a carbide gradient layer is deposited on the surface of the pure tantalum sheet.
[0061] Comparative Example 4
[0062] The difference between Comparative Example 4 and Example 6 is that the steps S2 and S3 are missing, and only a diamond layer is deposited on the surface of the Ta-2.5W tantalum alloy.
[0063] Comparative Example 5
[0064] The difference between Comparative Example 5 and Example 6 is that the S3 step is missing and the diamond layer is deposited directly on the carbide gradient layer.
[0065] Comparative Example 6
[0066] The difference between Comparative Example 6 and Example 6 is that the S3 and S4 steps are missing, and only a carbide gradient layer is deposited on the surface of the Ta-2.5W tantalum alloy.
[0067] The materials prepared in the above examples and comparative examples were subjected to nanoindentation hardness test, solid particle scouring test, coating adhesion test, friction coefficient test, and thermal shock resistance test. The test results are shown in Table 1. The test methods are as follows:
[0068] Microhardness test: A Bruker TI980 TriboIndenter nanoindenter was used. The tip radius of the indenter was about 50 nm, the load and displacement resolutions were 1 μN and 0.03 nm, and a 10-second hold time was used between loading and unloading cycles. To avoid errors, each sample was measured 5 times and the average value was taken.
[0069] Solid particle scouring test coating bonding strength: Solid particles repeatedly impact the surface of the workpiece, so that the coating material is gradually removed from the substrate surface to determine the anti-scouring performance of the diamond coating. The scouring time is 150s, and the scouring width of the diamond coating is measured by microscopic observation to determine the anti-scouring performance of the diamond coating. The smaller the scouring width, the greater the bonding strength.
[0070] Friction coefficient test: Rtec MFT-5000 friction and wear tester was used to carry out linear reciprocating friction and wear test on the substrate and the samples after nitriding treatment. The friction and wear test used a GCr15 steel ball with a diameter of 6 mm, set the normal load to 5N, the friction rate to 0.032m / s, the amplitude to 5mm, and the friction time to 1800s.
[0071] Thermal shock resistance test: A vertical tube furnace is used to conduct a thermal shock cycle test from room temperature to 1273K on the coating sample. Before the test, the coating sample is dried in a drying oven for 4 hours. After cooling, it is weighed using an electronic analytical balance with an accuracy of 0.0001g. After the temperature of the tube furnace rises to 1273K, it is kept warm for 30 minutes to ensure uniform temperature. The sample is quickly placed in the furnace and kept for 5 minutes, then taken out immediately and placed in an air environment to cool for 5 minutes. This is one thermal shock cycle. After 5 consecutive thermal shock cycles, the sample is weighed after cooling to , and the weight loss curve of the sample after a certain number of thermal shocks can be obtained by repeating this cycle. The thermal shock resistance of the coating sample can be judged 20 times by the weight loss of the coating sample.
[0072] Table 1 Coating performance test results
[0073]
[0074] As shown in Table 1, compared with Comparative Example 1, the hardness of the composite layer samples of carbide transition layer / diamond layer of Examples 1 to 7 is increased by 259%-331%, the coating bonding performance is improved by 290%-342%, the friction coefficient is reduced to one-sixth, and the thermal shock weight loss is reduced to one-half, indicating that the preparation method of the present application can significantly improve the hardness of the material, the coating bonding force and the erosion resistance, while the friction coefficient is also significantly reduced, and the thermal shock resistance is significantly improved.
[0075] The surface carburizing treatment of tantalum and its alloys is helpful for the next step of diamond deposition, and it is easier to form a high-quality and thick diamond film. At the same time, the transition of carbon elements is conducive to the stability of the overall material, improves mechanical properties, reduces friction coefficient, and enhances thermal shock resistance. In comparative example 1, there is no carburized transition layer structure. The bonding between diamond and tantalum substrate mainly depends on weak surface contact, and the bonding at the atomic level is not achieved. The bonding strength is insufficient, and interface detachment or delamination is prone to occur, resulting in a significant reduction in the bonding strength of the coating. In addition, the diamond-tantalum surface contact forms a microscopic layered structure. There is a large difference in physical and chemical properties between the diamond layer and the tantalum substrate. When subjected to thermal effects in the test environment, stress will occur, resulting in insufficient overall bonding strength of the coating. At the same time, the adhesion rate of diamond deposition is very low, and it is difficult to nucleate and grow, resulting in poor quality of the diamond film, thereby reducing the density and hardness of the material.
[0076] In Comparative Example 2, the surface laser processing of the carburized layer was not performed, and no micro-nano structure was formed in the carburized layer, thereby losing the microscopic interlocking structure with the diamond layer. The insufficient density of the overall material and the lack of the buffer stress area will lead to micropores and defects in the coating microstructure, which cannot alleviate thermal mutations and shocks, thereby reducing the hardness and coating bonding in the test environment, and reducing thermal shock resistance. In addition, when the density is insufficient, wear and surface unevenness are more likely to occur during friction, thereby increasing the friction coefficient.
[0077] The present invention couples the advantages of femtosecond laser precision machining technology and microwave plasma chemical vapor deposition technology, proposes a structural design of a film-based transition layer, and the prepared carbide transition layer / diamond layer composite layer structure has a structure with a gradual change in composition; a micro-nanoscale pretreatment process is introduced, and a highly ordered surface micro-nanostructure greatly improves the film-based bonding force, alleviates the impact of thermal effects during the use of the material, realizes the transition of the film-based physicochemical properties, reduces internal stress, improves bonding force, and has excellent thermal shock resistance, thereby preparing a diamond film with a dense and smooth surface and ultra-high hardness.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite layer structure of a carbide transition layer-diamond layer, characterized in that: include: Tantalum matrix; A carbide gradient layer deposited on the surface of the tantalum substrate, wherein the C atom content in the carbide gradient layer gradually decreases toward the tantalum substrate; A diamond layer is deposited on the surface of the carbide gradient layer.
2. A composite layer structure of a carbide transition layer-diamond layer as claimed in claim 1, characterized in that: A plurality of grooves are etched on the surface of the carbide gradient layer.
3. The composite layer structure of a carbide transition layer and a diamond layer according to claim 1, characterized in that: The carbide gradient layer comprises TaC and Ta2C.
4. The composite layer structure of a carbide transition layer-diamond layer according to claim 1, characterized in that: The tantalum substrate is a pure tantalum sheet or a tantalum alloy.
5. The method for preparing a composite layer structure of a carbide transition layer-diamond layer according to claim 2, characterized in that: The following steps are involved: S1, tantalum substrate surface polishing; S2, carbonization treatment of tantalum substrate: placing the tantalum substrate in a reaction chamber of a microwave plasma chemical vapor deposition device, bombarding the substrate with hydrogen plasma, etching and removing surface impurities, and then introducing carbon source gas to deposit a carbide gradient layer; S3, placing the carburized tantalum substrate in a femtosecond laser device, and etching a plurality of transverse and longitudinal intersecting grooves on the surface of the carbide gradient layer; S4, placing the tantalum substrate after etching in step S3 in a reaction chamber of a microwave plasma chemical vapor deposition device, introducing a carbon source gas to deposit a diamond layer, and obtaining a composite layer of a carbide transition layer-diamond layer on the tantalum substrate.
6. The method for preparing a composite layer structure of a carbide transition layer-diamond layer according to claim 5, characterized in that: In step S2, the reaction chamber is evacuated to below 1 Pa, 300 sccm of hydrogen is introduced, the microwave power is adjusted to 4250-5000 W, the chamber pressure is 18-22 KPa, the temperature is 600-750° C., and the substrate is bombarded by hydrogen plasma for 15-25 minutes to etch and remove impurities.
7. The method for preparing a composite layer structure of a carbide transition layer-diamond layer according to claim 5, characterized in that: During the carbonization treatment in step S2, the microwave power is 4250-5000W, the deposition time is 3-6h, the carbonization deposition temperature is 850-1050°C, and the atomic percentage of carbon atoms in the reaction chamber is 0.5%-2%.
8. The method for preparing a composite layer structure of a carbide transition layer-diamond layer according to claim 5, characterized in that: In step S3, the laser power is 10-15 W, the scanning period is 20-30 μm, the scanning speed is 5-8 mm / s, and the number of scans is 4-6 times.
9. The method for preparing a composite layer structure of a carbide transition layer-diamond layer according to claim 5, characterized in that: In step S3, the groove depth is 4-6 μm.
10. The method for preparing a composite layer structure of a carbide transition layer-diamond layer according to claim 5, characterized in that: In step S4, when the diamond layer is deposited, the atomic percentage of carbon atoms in the reaction chamber is 2.5%-5%, the chamber pressure is 8-10KPa, the microwave power is 4250-5000W, the deposition time is 4-8h, and the deposition temperature is 750-850°C.
Citation Information
Patent Citations
Diamond / W-C gradient structure composite coating and preparing method thereof
CN101487121A
Diamond-like carbon film of gradient structure and preparation method thereof
CN106521493A
Tantalum-based boron-doped diamond semiconductor composite coating material as well as preparation method and application thereof
CN117684142A
Super wear-resistant and corrosion-resistant gradient composite coating and preparation method thereof
CN118256864A
Heterogeneous carbide or nitride coating with tantalum-titanium embedded structure and preparation method thereof
CN118996393A